Benjamin Netanyahu's state visit to India. Issue 5 (3rd September 2019) - Roy, Pradipta
ABSTRACT: A six-day visit by PM Benjamin Netanyahu to India on 14–19 January 2018 marked a new apogee in the renewed relationship between two old civilizations. It was a reciprocal visit to PM Narendra Modi's visit to Israel in July 2017 to celebrate the Silver Jubilee year of the 'Diplomatic Normalisation' between the two states. Netanyahu's visit took place not only against the backdrop of this enthusiasm, but also had concrete economic and political goals given that just a month before the visit New Delhi cancelled a $500 arms deal with Israel and voted against the Jewish state in the UNGA on the Jerusalem question. Through five public addresses, three media interviews and one road show, Netanyahu attempted to break longstanding anti-Israel stereotypes and show the Indian masses that they could be beneficiaries of Israel's innovation and technological advancement. Amplified by a string of economic, high-tech, agricultural, and defence agreements, Netanyahu's visit proved to be a success, whose positive implications will affect the bilateral relations for years to come.